Applications of Stochastic Simulations in Inventory Management Optimization: Cost Accounting Perspectives - Choi, Yong; Li, Ji; Wu, Di (Journal of Applied Business and Economics, 2018)
Inventory Management in cost accounting is important since materials or merchandise costs account for a large portion of total costs of manufacturing and merchandising companies. An effective and efficient system of inventory management can hence be critical for controlling business costs and to improve profitability. This paper focuses on applications of nonlinear optimization and stochastic models to study various issues in inventory management, especially from cost accounting perspectives. The applications illustrated in this paper can be fully implemented in real world inventory management situations using a spreadsheet software tool, and can also be integrated into the cost accounting curriculum.